Fingerprint Sweat Pore Density in Patients with Oligodontia: A Controlled Clinical Trial - Jonas Q. Schmid; Jens Reimann; Claudius Middelberg; Ole Oelerich; Thomas Stamm; Ariane Hohoff (Biomedicines)
Background/Objectives: There is a lack of evidence for the relationship between sweat pores and tooth agenesis. The aim of this study was to compare sweat pore density on fingertips between a group of patients with oligodontia and a control group without tooth agenesis. Methods: This parallel-group controlled clinical trial included 28 patients. Fourteen patients (f/m 9/5; mean age 13.5 ± 3.5 years) with ≥6 congenitally missing permanent teeth, excluding third molars (M3), were enrolled in the study group. The matched control group consisted of 14 patients (f/m 9/5; mean age 12.8 ± 1.8 years) without tooth agenesis. Impressions of 168 fingertips (left and right index, middle, and ring fingers) of the participating subjects were taken and examined using a scanning electron microscope with a 5.85 mm × 4.29 mm region of interest at the center of the fingertip. The primary outcome was the pore-to-pore distance (μm) on a dermal ridge, and the secondary outcome was the number of sweat pores per cm2, while pore numbers were adjusted for individual body surface area (BSA). Results: There were no statistically significant differences in age, height, weight, and BSA between the groups. The study group had 11.07 ± 4.03 missing teeth, excluding M3. There was a statistically significant difference (p = 0.006) in the distance between adjacent pores on a dermal ridge between the study and control groups (354.89 <semantics>±<mspace width="0.222222em"></mspace></semantics>32.41 μm vs. 340.31 <semantics>±<mspace width="0.222222em"></mspace></semantics>39.04 μm). The unadjusted pore numbers showed a statistically significant difference between the groups, but after adjustment for BSA, this difference was no longer present. Conclusions: Patients with oligodontia differed from subjects without tooth agenesis in the distance between two adjacent sweat pores on a dermal ridge. However, the differences were small and of limited clinical significance. Increased pore distance appears to be a better predictor of oligodontia/ectodermal dysplasia than pore number.